Electromagnetic Induction in the Earth - Niblett, E. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary The study of electromagnetic induction in the earth has provided a geophysical method for using magnetic and electric field variations observed on the surface to interpret electrical conductivity and earth structure over a wide range of depths. Analysis of geomagnetic data on a world-wide basis has shown that both conductivity and internal temperature increase rapidly in the mantle, between depths of 300 and 1000 km. In addition many localized zones of high conductivity have been found in the crust and upper mantle. Important anomalies of this type are located in the Cordillera regions of North and South America, in the Japanese Arc, North Germany, and in the Canadian Arctic to mention only a few. These large anomalies, some of them many hundreds of kms in extent, are often found near continental margins or near old plate boundaries. They appear to be associated in a fundamental way with the development of mobile belts and their study is becoming important in our understanding of global tectonics.